Performance evaluation based on economic value added in transportation companies - Alfian Lalo; Diyah Sukanti Cahyaningsih (University of Merdeka Malang, 2022)
Financial performance can be measured by various measurement methods, one of which is Economic Value Added (EVA). EVA is a performance measurement that considers the benefits based on the added value that can be obtained. Measuring the performance of transportation companies is currently very necessary considering that technological developments have brought many changes to the transportation industry. This research was conducted at PT Blue Bird Tbk. Secondary data was obtained through annual financial reports for the 2019-2021 period on the IDX website and supporting websites using the documentation method. Data were analyzed in four stages of EVA Performance measurement which consisted of NOPAT (Net Operating After Taxes), Invested Capital, WACC (Weight Average Cost of Capital), and Capital Charge. The results of the study using the EVA method obtained an EVA value 0 (negative value), meaning that the company was not successful in producing economic added value. The decline in the value of EVA is suspected to be due to several factors such as the COVID-19 pandemic where restrictions on community activities and the availability of online transportation were imposed.